2021
DOI: 10.20944/preprints202102.0537.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Review of Damage, Void Evolution, and Fatigue Life Prediction Models

Abstract: This paper aims to provide an overall review of degradation, damage evolution and fatigue models in the literature of various engineering materials, mostly metals, and composites.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The fatigue failure of solder joint under TCL is the process of cracks initiation and propagation, which is induced by the accumulation of strain‐based variables or the inelastic energy 48–52 . Chen and Pang 49 developed a strain‐based fatigue life model for solder joint under TCL, which is defined as follows: Nfmnormalϵitalicin=A where Nf is the fatigue lifetime, normalϵitalicin is the increment of strain‐based variables under one cycle, and A and m are material parameters with positive values.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatigue failure of solder joint under TCL is the process of cracks initiation and propagation, which is induced by the accumulation of strain‐based variables or the inelastic energy 48–52 . Chen and Pang 49 developed a strain‐based fatigue life model for solder joint under TCL, which is defined as follows: Nfmnormalϵitalicin=A where Nf is the fatigue lifetime, normalϵitalicin is the increment of strain‐based variables under one cycle, and A and m are material parameters with positive values.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The fatigue failure of solder joint under TCL is the process of cracks initiation and propagation, which is induced by the accumulation of strain-based variables or the inelastic energy. [48][49][50][51][52] Chen and Pang 49 developed a strain-based fatigue life model for solder joint under TCL, which is defined as follows:…”
Section: Fatigue Indicator Parametermentioning
confidence: 99%
“…The GTN model has been also widely applied or extended for modeling the ductile fracture of other metals such as steel [16,17], Al [18][19][20], Mg [21], and under a broad range of stress states [22][23][24]. More about the GTN model and its modifications can be referred to from a recent review by Lee and Basaran [25]. However, relatively few studies have been reported to probe the failure behaviors and thresholds of P/M superalloys under different TMP parameters by employing FEA with the GTN damage model.…”
Section: Introductionmentioning
confidence: 99%
“…It is no wonder that there are voices stating that the common fatigue life estimation procedures „ … primarily rely on the test data curve to fit the empirical void/damage evolution function…These empirical models are popular for engineering applications due to their simplicity . Still , the identification of parameters is costly , time‐consuming , and lacks any scientific basis due to a lack of physical and mathematical foundations” 8 and that a completely different solution must be found. If the common procedure of fatigue life estimation is assessed, the multitude of various effects, intertwined but solved separately, is really striking.…”
Section: Introductionmentioning
confidence: 99%